Pengetahuan dan Sikap Ibu Hamil Trimester I terhadap Hiperemesis Gravidarum di PMB Dina Sari Marpaung, Tanjung Balai 2023 - Erni Juwita Pasaribu; Retno Wahyuni; Ninsah Mandala Putri Sembiring; Rasmi Manullang; Hotnida Nasution; Juliyanti Pasaribu (An-Najat, 2023)
Nausea and vomiting are often early signs of pregnancy for the general public, especially due to long menstrual cycles. Therefore, some pregnant women only realize their pregnancy after experiencing these symptoms. Nausea and vomiting are common conditions in pregnancy, but if they occur more than ten times a day, this condition is categorized as hyperemesis gravidarum or chronic nausea and vomiting (Manuaba, 2010). Hyperemesis gravidarum can cause carbohydrate reserves in the body to be used up as energy, so that the body begins to use fat and protein reserves. As a result of imperfect fat burning, ketone bodies are formed in the blood, which can worsen clinical symptoms (Manuaba, 2010). This study used an observational analytical method with a cross-sectional design, where observation and measurement of dependent and independent variables were carried out simultaneously (Sastroasmoro, 2014). The purpose of this study was to determine the relationship between maternal knowledge and attitudes regarding hyperemesis gravidarum with the incidence of hyperemesis gravidarum at PMB Dina Sari Marpaung, Semula Jadi Village, Tanjung Balai City. Based on the description, the researcher is interested in examining the relationship between knowledge and attitudes of pregnant women in the first trimester regarding hyperemesis gravidarum at PMB Dina Sari Marpaung, Semula Jadi Village, Tanjung Balai City.